Implementation of Elliott wave theory - Balam Krishnakanth (2009)
Technical analysis is widely used by traders to predict future market movements. The Elliott Wave Theory is a form of technical analysis that was formulated by Ralph Nelson Elliott in the 1930s. He observed that crowd behavior trends and reverses in recognizable patterns, which he termed as waves. He quantified these seemingly random waves of price activity and classified them into particular wave structures.